Dynamics of elastic plastic shear frames with secondary structures shake table and numerical studies. - Adam, Christoph (Earthquake engineering & structural dynamics.)
Results from experimental and numerical studies of earthquake excited small scale primary secondary structures are presented. The primary structure considered is a plane three storey shear frame with a fundamental frequency of 5.5 Hz. The columns of the first floor are built with soft aluminium and they are stressed beyond its linear range of behaviour. After each test the elastic plastic columns are replaced by a new set of undeformed virgin aluminium bars. The elastic plastic shear frame is tested with and without an attached secondary structure. The secondary structure is modelled as an elastic SDOF oscillator, and its natural frequency is tuned to the fundamental frequency of the shear frame. Alternatively, the oscillator is mounted on the horizontal beam of the second and third floor. The base excitation of the structural model is characterized by a broad band random process with constant spectral density in a frequency range between 3 and 30 Hz. In the numerical study, the digital recorded acceleration of the base excites the mechanical model of the investigated structures. Numerical outcomes assuming fictitious unlimited elastic material behaviour of the shear frame are set in contrast to results from experiments and computational simulations where the measured non linear force displacement relation of the elastic and computational simulations where the measured non linear force displacement relation of the elastic plastic floor is approximated by a piecewise linear curve. The effect of elastic plastic materials on the dynamic interaction between primary and secondary structure is shown and the difference to unlimited elastic material behaviour is worked out in detail.